2010
DOI: 10.1029/2010gl043798
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation of total column BrO during Arctic spring

Abstract: [1] Emission of bromine from sea-salt aerosol, frost flowers, ice leads, and snow results in the nearly complete removal of surface ozone during Arctic spring. Regions of enhanced total column BrO observed by satellites have traditionally been associated with these emissions. However, airborne measurements of BrO and O 3 within the convective boundary layer (CBL) during the ARCTAS and ARCPAC field campaigns at times bear little relation to enhanced column BrO. We show that the locations of numerous satellite B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
162
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(180 citation statements)
references
References 35 publications
17
162
1
Order By: Relevance
“…However, these hypotheses are questionable because of the possible overall presence of BrO in the troposphere and the longitudinal and latitudinal inhomogeneity of stratospheric BrO. The latter point is crucial as it has recently been argued that the stratospheric BrO column variability could be larger than previously thought, being exacerbated by the supply of significant amounts of Br y in the lower stratosphere from short-lived bromocarbons (Salawitch et al, 2010). One possibility to estimate stratospheric BrO columns at the global scale is to use the BrO profiles measured by the SCIAMACHY instrument in its limb mode (see e.g.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, these hypotheses are questionable because of the possible overall presence of BrO in the troposphere and the longitudinal and latitudinal inhomogeneity of stratospheric BrO. The latter point is crucial as it has recently been argued that the stratospheric BrO column variability could be larger than previously thought, being exacerbated by the supply of significant amounts of Br y in the lower stratosphere from short-lived bromocarbons (Salawitch et al, 2010). One possibility to estimate stratospheric BrO columns at the global scale is to use the BrO profiles measured by the SCIAMACHY instrument in its limb mode (see e.g.…”
Section: Introductionmentioning
confidence: 65%
“…The approach is similar in concept to the correction used for the retrieval of tropospheric NO 2 columns by Richter et al (2005). Here the correction is based on the fact that the variations in stratospheric Br y are controlled by atmospheric dynamics in a way that matches closely the O 3 fluctuations, as clearly established by Theys et al (2009b) and further demonstrated by Salawitch et al (2010) using measured O 3 and BrO vertical columns. We assume that in conditions described below the slope of a BrO versus O 3 regression plot is fully controlled by stratospheric BrO.…”
Section: Stratospheric Bro Correctionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, novel observations of BrO (Liao et al, 2011) have shown that "BrO clouds" tend to be distributed homogeneously over scales of a few kilometres during ODEs, while Salawitch et al (2010) found that BrO columns are correlated with the height of the tropopause, although some "hotspots" are related to free-tropospheric or stratospheric intrusions.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…The low chlorine level of 0.8 ppb represents both a pre-industrial chlorine value (when CH 3 Cl at 0.6 ppb was the major chlorine carrier), as well as a likely chlorine level towards the end of the century, on a Montreal Protocol trajectory towards "recovery", according to projected mitigation scenarios for 2100. For stratospheric inorganic bromine, we chose three levels of ∼ 10, ∼ 15 and ∼ 23 ppt to represent approximately a low (∼ pre-industrial era, when ice core data suggest a methyl bromide concentration of about 5 ppt; Saltzman et al, 2008), medium and high (∼ present-day) level, respectively. These values all include ∼ 5 ppt from VSLS (as described above), with the remaining Br y coming from long-lived halons and CH 3 Br.…”
Section: Model and Experimentsmentioning
confidence: 99%